Menstrual Disorders Following Tubal Ligation - Hyaam A Lafta Al-Assadi; Sajida Al-Rubai; Huda Qahtan Fouad (Institute of Medico-legal Publications Pvt Ltd, 2022)
This is a prospective case —control study that was carried out at Basrah Maternity and Child Hospital from 1st ofJanuary 2019 till 1st of June 2020.Objective: The objective of this study is to find an association between menstrual disorders and bilateral tuballigation.Design: It is a case-control study of 30-45 years old women setting at Basra governorate.Material and Method: Three hundred twenty four patients were included in the study of age [30- 45] years, theywere divided into two groups. group one [156] with history of tubal ligation 1-3 years ago compared to a controlgroup of [168] without tubal ligation a non-medical contraception was used.Result: In group one menorrhagia was more common when compared with non-tubal ligation group [68.5% Vs29.7] respectively and the difference was statistically significant.Conclusion: Our findings show that menstrual disorders were more common in women tubal ligation. This studyshows that tubal ligation may influences irregular menstruation and causes menorrhagia. In other words, tuballigation is associated with an increased risk of menstrual disorders.